ssrA (tmRNA) Plays a Role in Salmonella enterica Serovar Typhimurium Pathogenesis - Julio, Steven M. (American Society for Microbiology, 2000)
Escherichia coli ssrA encodes a small stable RNA molecule, tmRNA, that has many diverse functions, including tagging abnormal proteins for degradation, supporting phage growth, and modulating the activity of DNA binding proteins. Here we show that ssrA plays a role in Salmonella enterica serovar Typhimurium pathogenesis and in the expression of several genes known to be induced during infection. Moreover, the phage-like attachment site, attL, encoded within ssrA, serves as the site of integration of a region of Salmonella-specific sequence; adjacent to the 5′ end of ssrA is another region of Salmonella-specific sequence with extensive homology to predicted proteins encoded within the unlinked Salmonella pathogenicity island SPI4. S. enterica serovar Typhimurium ssrA mutants fail to support the growth of phage P22 and are delayed in their ability to form viable phage particles following induction of a phage P22 lysogen. These data indicate that ssrA plays a role in the pathogenesis of Salmonella, serves as an attachment site for Salmonella-specific sequences, and is required for the growth of phage P22.